1974
DOI: 10.1111/j.1550-7408.1974.tb03641.x
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle of Isospora canis Nemeséri, 1959 in the Dog*

Abstract: SYNOPSIS The life cycle of I. canis Nemeséri, 1959 was studied in experimentally infected dogs. Freshly sporulated oocysts were ovoid and 34–40 × 28–32 μm. The endogenous stages were found directly beneath the epithelium of the distal portion of the small intestinal villi. Most of the endogenous stages were in the lower 1/3 of the small intestine, but occasionally they were found in other portions of the small intestine. Three asexual generations were present. First‐generation schizonts were 16–38 × 11–23 μm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 7 publications
5
36
1
Order By: Relevance
“…Nemeséri (1960) found that 5 ϫ 10 3 oocysts of a Hungarian isolate of C. canis were not pathogenic for dogs, but an inoculum of 5 or 8 ϫ 10 4 oocysts produced clinical coccidiosis. In contrast, severe clinical disease was not produced in 25, 6-wk-old or 6, 8-wkold pups inoculated with 1-1.5 ϫ 10 5 C. canis oocysts (Lepp and Todd, 1974) isolated in dogs from Illinois. The pathoge-FIGURE 5.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Nemeséri (1960) found that 5 ϫ 10 3 oocysts of a Hungarian isolate of C. canis were not pathogenic for dogs, but an inoculum of 5 or 8 ϫ 10 4 oocysts produced clinical coccidiosis. In contrast, severe clinical disease was not produced in 25, 6-wk-old or 6, 8-wkold pups inoculated with 1-1.5 ϫ 10 5 C. canis oocysts (Lepp and Todd, 1974) isolated in dogs from Illinois. The pathoge-FIGURE 5.…”
Section: Discussionmentioning
confidence: 87%
“…Sporulation time: Sporulation is complete in 48 hr at 20 C and 16 hr at 30 or 35 C (Lepp and Todd, 1976).…”
Section: Location In Hostmentioning
confidence: 99%
See 3 more Smart Citations